2015
DOI: 10.11648/j.ajhr.20150306.15
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram, Biochemical Reactions and Biotyping of Biofield Treated <i>Providencia rettgeri</i>

Abstract: Providencia rettgeri (P. rettgeri) is the key organism for gastrointestinal tract infections due to its high virulence properties. The current study was designed to investigate the effect of Mr. Trivedi's biofield energy treatment on P. rettgeri in lyophilized as well as revived state for antimicrobial susceptibility pattern, biochemical characteristics, and biotype number. The lyophilized strain of P. rettgeri (ATCC 9250) was divided into two parts, Group (Gr.) I: control and Gr. II: treatment. After biofield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This energy can be harnessed and transmitted by the experts into living and non-living things via the process of Biofield Energy Healing. Biofield Energy Treatment (The Trivedi Effect ® ) has been published in numerous peer-reviewed science journals with significant outcomes in many scientific fields such as cancer research [16,17], microbiology [18][19][20][21], biotechnology [22,23], pharmaceutical science [24][25][26][27], agricultural science [28][29][30][31], materials science [32][33][34][35], nutraceuticals [36,37], skin health [38,39], human health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…This energy can be harnessed and transmitted by the experts into living and non-living things via the process of Biofield Energy Healing. Biofield Energy Treatment (The Trivedi Effect ® ) has been published in numerous peer-reviewed science journals with significant outcomes in many scientific fields such as cancer research [16,17], microbiology [18][19][20][21], biotechnology [22,23], pharmaceutical science [24][25][26][27], agricultural science [28][29][30][31], materials science [32][33][34][35], nutraceuticals [36,37], skin health [38,39], human health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…This energy can be harnessed and transmitted by the experts into living and non-living things via the process of Biofield Energy Healing. Biofield Energy Treatment (The Trivedi Effect ® ) has been published in numerous peer-reviewed science journals with significant outcomes in many scientific fields such as cancer research [16,17], microbiology [18][19][20][21], biotechnology [22,23], pharmaceutical science [24][25][26][27], agricultural science [28][29][30][31], materials science [32][33][34][35], nutraceuticals [36,37], skin health, human health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23,24], nutraceuticals [25,26], organic compounds [27][28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate displays the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%